Lincoln Cathedral
On Palm Sunday in 1185 the Norman Cathedral at Lincoln was destroyed by an earthquake, which left only the west front undamaged. Complete rebuilding was required, and under the inspiration of Bishop Hugh of Avalon, brother of the then Bishop of Wells, a new and important design emerged. Every aspect of Romanesque was rejected. Even the simplicity, which is such a feature of the work at Wells, was set aside, and, commencing with the choir, a new and truly Gothic building of enormous cost arose.